The crisis-events and reassembled ethnolinguistic-cum-environmentalist subjects in Inner Mongolia. - Baioud, Gegentuul (Central Asian Survey, 2025)
This paper explores the emergence of ethnolinguistic-cum-environmentalist subjects in two crisis events as they are animated by the polarized qualia of darkness versus luminosity and of silence versus sonorousness. I combine an analysis of artistic works by Mongols with ethnographic evidence to show how the two critical laments of nationalism, the Mongolian language and grasslands, are interlocked and fused as the qualia of darkness and silence or their opposite sensuous qualities imposed onto a number of objects ranging from animals, rivers, future time-space, a fearless hero to a sudden gap in everyday conversations. That is, I draw on the concept of qualia to account for the formation of an intensified and maximally-existing subject as crisis-events unfold in the context of environmental destruction and language assimilation in Inner Mongolia.